Ventilation changes in the western North Pacific since the last glacial period - Y. Okazaki; T. Sagawa; H. Asahi; K. Horikawa; J. Onodera (Climate of the Past, 2012)
We reconstructed the ventilation record of deep water at 2100 m depth in the mid-latitude western North Pacific over the past 25 kyr from radiocarbon measurements of coexisting planktic and benthic foraminiferal shells in sediment with a high sedimentation rate. The 14C data on fragile and robust planktic foraminiferal shells were concordant with each other, ensuring high quality of the reconstructed ventilation record. The radiocarbon activity changes were consistent with the atmospheric record, suggesting that no massive mixing of old carbon from the abyssal reservoir occurred throughout the glacial to deglacial periods.